The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1371/journal.pone.0100791
|View full text |Cite
|
Sign up to set email alerts
|

Hijacking of Host Cellular Functions by an Intracellular Parasite, the Microsporidian Anncaliia algerae

Abstract: Intracellular pathogens including bacteria, viruses and protozoa hijack host cell functions to access nutrients and to bypass cellular defenses and immune responses. These strategies have been acquired through selective pressure and allowed pathogens to reach an appropriate cellular niche for their survival and growth. To get new insights on how parasites hijack host cellular functions, we developed a SILAC (Stable Isotope Labeling by Amino Acids in Cell culture) quantitative proteomics workflow. Our study foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 60 publications
(66 reference statements)
1
16
0
Order By: Relevance
“…The RNA‐binding ability of IFIT2 protein is required for antiviral activity and to promote apoptosis (Reich, ). Further, IFIT2 is also known to modulate the microtubule network implicated in cell reorganization during Anncaliia algerae infection as a host response to clear infection (Panek et al, ). The cytokines CCL5 and IL4 are part of the cascade of events leading to efficient parasite control in Leishmania major (Santiago et al, ) and Listeria (Kaufmann, Emoto, Szalay, Barsig, & Flesch, ) infections, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The RNA‐binding ability of IFIT2 protein is required for antiviral activity and to promote apoptosis (Reich, ). Further, IFIT2 is also known to modulate the microtubule network implicated in cell reorganization during Anncaliia algerae infection as a host response to clear infection (Panek et al, ). The cytokines CCL5 and IL4 are part of the cascade of events leading to efficient parasite control in Leishmania major (Santiago et al, ) and Listeria (Kaufmann, Emoto, Szalay, Barsig, & Flesch, ) infections, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The RNA-binding ability of IFIT2 protein is required for antiviral activity and to promote apoptosis (Reich, 2013). Further, IFIT2 is also known to modulate the microtubule network implicated in cell reorganization during Anncaliia algerae infection as a host response to clear infection (Panek et al, 2014). The cytokines CCL5 and IL4 are part of the cascade of events leading to efficient parasite control in Leishmania major (Santiago et al, 2004) and Listeria (Kaufmann, Emoto, Szalay, Barsig, & Flesch, 1997) Our transcriptome data from P. berghei-infected HepG2 cells (Spz+), when compared to previous study of transcriptional landscape of murine hepatoma (Hepa1-6) cells infected with P. berghei sporozoites (Albuquerque et al, 2009), revealed similarity in the differential expression of several host genes such as AARS, CHAC1, DPP7, GPR137, KIF5C, KLF4, MAF, NR4A2, NRP, PROC, PTPN14, and SLC16A4.…”
Section: Ifng Activates Jak/stat Pathway Leading To Synthesis Of Irf1mentioning
confidence: 99%
“…The innate immune response to this microbial colonisation is increased urothelial cell shedding, which may be promoted by mast cells [41]. The shed cells may be colonised or unaffected, but the proportion of parasitised cells in the face of infection would be expected to increase [42]. This sediment, a mixture of white cells, epithelial cells and debris, is likely to collect under the influence of gravity at the bladder base, forming a sampling target that should not be influenced by dilution effects.…”
Section: Discussionmentioning
confidence: 99%
“…This in turn could occasionally yield genotypes that can jump to new host populations or even to new host species, as suggested for filamentous plant pathogens (Raffaele and Kamoun, 2012). Furthermore, recent study also suggests that A. algerae could use a TE as a lure strategy to escape the host innate immune system (Panek et al, 2014). Therefore, TEs may play an important role not solely in modulating the microsporidian genome architecture but also in the capacity of these parasites to infest multiple hosts and especially to adapt to new hosts.…”
Section: Potential Impacts Of Transposable Elements On Microsporidianmentioning
confidence: 96%